2020
DOI: 10.1097/rhu.0000000000001562
|View full text |Cite
|
Sign up to set email alerts
|

The Pitfall in Differential Diagnosis of Musculoskeletal Symptoms in Children

Abstract: S curvy is a well-known disorder caused by vitamin C deficiency. Its clinical spectrum is quite variable and can mimic several infectious, inflammatory, or oncological conditions. These factors contribute to frequent misdiagnosis of scurvy in pediatric age. Patients often require medical attention for musculoskeletal symptoms and undergo an extensive workup before final diagnosis. In the present case series, we describe 4 children diagnosed with scurvy in the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…Musculoskeletal complaints were the most frequently described manifestations (92%); particularly, severe pain in the lower limbs (88%) with refusal to walk (73%) and limping (31%). These manifestations are present in a high but variable rate of patients with scurvy, ranging from 67% [ 44 ] to 100% [ 18 , 45 , 46 ] in the different series. Rarely, pain in the back (1%) or the upper limbs (1%) was referred, too.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Musculoskeletal complaints were the most frequently described manifestations (92%); particularly, severe pain in the lower limbs (88%) with refusal to walk (73%) and limping (31%). These manifestations are present in a high but variable rate of patients with scurvy, ranging from 67% [ 44 ] to 100% [ 18 , 45 , 46 ] in the different series. Rarely, pain in the back (1%) or the upper limbs (1%) was referred, too.…”
Section: Resultsmentioning
confidence: 99%
“…Difficulty in diagnostic assessment and the differential diagnosis was underlined by several authors: 11 studies reported the interval between clinical onset and diagnosis, ranging from one week [ 47 ] to 2 years [ 48 ]; when available, the median interval was 2 months, calculated on 9 studies [ 4 , 5 , 18 , 45 , 46 , 49 , 50 , 51 , 52 ]. Thirty patients (18%) underwent invasive diagnostic exams: 11 bone marrow aspiration/biopsy, five bone biopsy, three gingival biopsies, two bone scintigraphy, two head CT scans, two chest-abdomen CT scans, two brain MRIs, one muscle biopsy and one lumbar puncture.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations